Evaluation of brown trout (Salmo trutta fario) fillets' shelf life: Fed with a humic supplemented diet. (September 2021) - Atamanalp, Muhammed; Ucar, Arzu; Kocaman, Esat Mahmut; Alak, Gonca
Highlights: The use of humic acid in seafood has been evaluated in terms of meat quality and shelf life. Humic acid application was not effective in chemical composition. It was effective in the mineral content of fillets. In terms of shelf life, 2 % humic acid supplement gave lower values ​​than control. Abstract: This research was designed to determine the shelf life of products obtained by using humic acid as a feed additive in trout culture. Accordingly, brown trouts ( Salmo trutta fario ) were fed with different levels of humic acid added feed for 90 days. At the end of the feeding trial, the chemical composition, mineral substance, color and texture analyzes were made in the obtained fillets. The shelf life of fillets was evaluated with physico-chemical [pH, Thiobarbituric Acid Reactive Substance (TBARS)], total volatile basic nitrogen (TVB-N)] and microbiological [psychrophilic bacteria, total mesophilic aerobic bacteria, lactic acid bacteria, Enterobacteriaceae, and Pseudomonas counts] parameters with 15 days of cold storage. It had been determined that humic acid is not effective in chemical composition, color and texture (p > 005), but has a significant effect at p < 0.05 level in mineral substance, pH, TBARS, TVB-N, and microbiological results. Although increases and decreases were determined in all analyzes' values ​​during the storage period, it was determined that the 2% humic acid applied group gave relatively lower values ​​at the end of the storage period in the microbiological and physico-chemical analysis results.